El Excentrico, 1980-06-01 & 1980-07-01 - Garcia, Bert:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2024)
June & July 1980 [Junio y Julio de 1980]. Ano 31, No. 3. Cover contains a portrait of celebrity Vicente Frenandez, who would be performing at San Jose for the Fourth of July. The headline reads, "Vicente Fernandez aqui en San Jose por el 4 de Julio" (transl: Vicente Fernandez here in San Jose for the 4th of July).